Analisis Faktor-Faktor Yang Mempengaruhi Literasi Keuangan Mahasiswa: Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Sumatera Utara - Murviana Koto (CERED Indonesia Institute, 2021)
Financial literacy is an issue that is still hotly discussed today. This is because skills in finance can lead a person to financial prosperity. The world of higher education contributes to the improvement of financial literacy, and this study wants to see how the factors of gender, age, parents' income and spending in college affect the financial literacy of students. This research was conducted on 498 students of the Faculty of Economics and Business using the accidental sampling method. Financial literacy was analyzed by descriptive analysis, and factor analysis was carried out by using Confirmatory Factor Analysis (CFA) using Structural Equation Model (SEM). The results of this study indicate that the factors of age, gender and parental income have a significant effect on student financial literacy, while the learning factor in college does not significantly affect student financial literacy.